2022
DOI: 10.1002/anie.202213281
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reductive Coupling of Vinyl Azaarenes and Alkynes via Photoredox Cobalt Dual Catalysis

Abstract: A visible light‐induced Co‐catalyzed highly regio‐ and stereoselective reductive coupling of vinyl azaarenes and alkynes has been developed. Notably, Hünig's base together with simple ethanol has been successfully applied as the hydrogen sources instead of commonly used Hantzsch esters in this catalytic photoredox reaction. This approach has considerable advantages for the straightforward synthesis of stereodefined multiple substituted alkenes bearing an azaarene motif, such as excellent regioselectivity (>20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 159 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Transmetalation from the Co­(II)–aryl intermediate to ZnX 2 generates the organozinc product. Here we show that the favorable thermodynamics of transmetalation from Co­(II) to Zn can be successfully merged with reductive C–C coupling to achieve an asymmetric synthesis of Zn metallacycles. In previous examples of imine and alkyne reductive coupling reactions, a terminal reductant such as H 2 or a H 2 surrogate is used, and the products contain a hydrogen atom at the site of the M–C bond .…”
mentioning
confidence: 95%
“…Transmetalation from the Co­(II)–aryl intermediate to ZnX 2 generates the organozinc product. Here we show that the favorable thermodynamics of transmetalation from Co­(II) to Zn can be successfully merged with reductive C–C coupling to achieve an asymmetric synthesis of Zn metallacycles. In previous examples of imine and alkyne reductive coupling reactions, a terminal reductant such as H 2 or a H 2 surrogate is used, and the products contain a hydrogen atom at the site of the M–C bond .…”
mentioning
confidence: 95%
“…Inspired by the pioneering research reported by the Xia et al . and our recent work on dual photoredox/cobalt catalysis, , we speculated whether the asymmetric photoinduced cobalt-catalyzed reductive coupling combined with the desymmetrization strategy could be applied to the synthesis of centrally and axially chiral biaryls (Figure c). The potential challenges for this strategy include: (1) simultaneous stereocontrol of central and axial chirality, (2) recognition of symmetrical aldehyde groups of biaryls and avoiding over-reduction, and (3) competitive processes, such as hydrogenation of aryl iodides.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group realized a photomediated cobalt-catalyzed asymmetric radical coupling reaction involving a DYKAT, with the combination of an octahedral cobalt coordination catalyst and a chiral sulfanilamide bisphosphine ligand, the key to achieving enantioselectivity. Inspired by this work and our interest in asymmetric photocatalysis , and cobalt catalysis, we envisaged the use of cobalt-catalyzed DYKATs to asymmetrically add heterobiaryl triflates to conjugated alkenes promoted by visible light, a plausible reaction mechanism for which is shown in Figure c. When irradiated with blue light, photoexcited 4CzIPN* accepts an electron from diethyl 1,4-dihydro-2,6-dimethyl-3,5-pyridinedicarboxylate (Hantzsch ester; HE) [ E 1/2 ox (HE/HE •+ ) = 0.51 V vs Fc + /Fc in MeCN] to afford the reduced 4CzIPN •– photocatalyst [E 1/2 red (4CzIPN/4CzIPN •– ) = −1.21 V vs SCE in MeCN], which reduces the Co­(II)/ L complex to the low-valent Co­(I)/ L species and regenerates 4CzIPN through single electron transfer.…”
Section: Introductionmentioning
confidence: 99%